Evaluation of the hypercholesterolemia care cascade and compliance with NCEP-ATP III guidelines in Iran based on the WHO STEPS survey - Djalalinia, Shirin; Khosravi, Sepehr; Yoosefi, Moein; Salahi, Sarvenaz; Varniab, Zahra Shokri; Golestani, Ali; Rezaei, Nazila; Kazemi, Ameneh; Dilmaghani-Marand, Arezou; Rezaei, Negar; Ghasemi, Erfan; Ahmadi, Naser; et al. (Lipids in health and disease, 2025)
INTRODUCTION: Noncommunicable diseases (NCDs), particularly cardiovascular disease (CVD), are the leading cause of death worldwide, with hypercholesterolemia being a major risk factor for CVD. This study evaluated the hypercholesterolemia care cascade in Iran-including prevalence, diagnosis, treatment coverage, and effectiveness-using the National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) guidelines. - METHODS: This cross-sectional study drew on data from the 2021 Iran STEPS survey, which employed a systematic cluster sampling of adults aged ≥ 18 years across all provinces in Iran. Hypercholesterolemia was defined per NCEP-ATP III thresholds (LDL ≥ 160 mg/dL, total cholesterol ≥ 240 mg/dL, HDL ≤ 40 mg/dL, or ongoing lipid-lowering therapy). Weighted descriptive statistics were calculated, and Poisson regression with robust variance estimated crude and adjusted prevalence ratios for optimal lipid control among those treated. The 10-year CVD risk was determined using the Framingham Risk Score, stratifying participants into low (< 10%), intermediate (10-20%), and high (> 20%) risk categories. - RESULTS: Out of 18,074 participants, 10,582 (55.32%, 95% CI: 54.29-56.35) met NCEP-ATP III criteria for hypercholesterolemia. Among these, only 20.61% (19.55-21.72) were receiving pharmacological treatment. Treatment coverage was notably lower in males (13.15%, 11.98-14.40) than females (29.12%, 27.35-30.96). Statins were the most commonly used medication (11.43% of males, 25.87% of females). Of those receiving treatment, 52.85% (females) and 53.93% (males) achieved optimal LDL, while 76.98% (females) and 81.06% (males) attained total cholesterol < 200 mg/dL. However, only 19.89% (females) and 3.97% (males) met the HDL > 60 mg/dL goal. The 10-year CVD risk was < 10% in 57.79% of participants, 10-20% in 33.27%, and > 20% in 8.94%. - CONCLUSION: Despite a high prevalence of hypercholesterolemia in Iran, treatment coverage remains suboptimal, particularly among males and working-age adults. Although most treated individuals achieve favorable LDL and total cholesterol levels, gaps persist in achieving optimal HDL targets. These findings underscore the need for strengthened screening, treatment, and adherence strategies-alongside broader preventive measures-to reduce the burden of hypercholesterolemia and CVD in Iran.
Gesehen am 17.02.2026